1.9‐GHz CMOS power amplifier using a current source to enhance its dynamic range. Issue 8 (August 2014) - Seo, Donghwan; Lim, Sung‐Hun; Ahn, Hyeong‐Joon; Park, Changkun
ABSTRACT In this work, we propose a 1.9‐GHz CMOS power amplifier using 0.18‐µm RF CMOS technology. The amplifier operates in switching mode. To enhance the dynamic range of the switching mode amplifier, we propose a structure for the power stage in which a current source is used. In low‐output power regions, the current source operates in the saturation region to limit the current flowing through the power stage of the amplifier and, hence, to enhance the dynamic range. Conversely, in high‐output power regions, the current source operates in the triode region to minimize the parasitic resistance induced by the transistor and, hence, to maximize the maximum output power. We designed a power amplifier to prove the feasibility of the proposed structure using the current source. From the measured results, we successfully verify the feasibility of the proposed topology. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1886–1891, 2014